Military Family Physicians' Practices and Perceptions About Reproductive Health Services for Deploying Women. Issue 5 (25th September 2018) - de Kanter, Caitlyn B; Roberts, Timothy A; Raiciulescu, Sorana; Ali, Syed M; Arnold, James J; Witkop, Catherine; Klein, David A
Abstract: Introduction: Incomplete or inadequate provision of contraceptive services to servicewomen can have a profound impact on military health, readiness, and financial outcomes. This study examined the reproductive health practices and perceptions among family medicine physicians caring for servicewomen. Materials and Methods: We conducted an anonymous survey of 568 registered attendees at the March, 2018 Uniformed Services Academy of Family Physicians annual meeting. The response rate was 52.8% and 69% of responders met inclusion criteria. Results: Our sample of family medicine physicians was 58.3% male and 85.3% Caucasian. In all, 18.3% were current residents, 42.9% graduated between 2008 and 2017, and 38.7% graduated before 2008. A previous deployment was reported by 55.1%. Among physicians with a deployment history, 20.8% reported difficulty prescribing contraception during deployment because they were unable to obtain a patient's desired method, 2.6% reported servicewomen not accessing contraception because of fear and stigma associated with sexual activity in the deployed setting, and 22.1% reported problems with both factors. Among physicians performing pre-deployment and other readiness visits for active duty servicewomen, 17.4% reported not discussing contraception at these encounters because of competing priorities and 1.5% because of ethical/religious concerns. Physicians who could offer more rapid access to subdermal implants (within 2 weeks) were more likely to discuss contraception (87.0% versus 64.7%, p = 0.005). When discussing the use of contraception in the deployed environment, 15.8% of physicians would not prescribe oral contraceptives, 12.3% would not prescribe intrauterine methods, and 14.3% would not prescribe subdermal implants. Physicians who previously deployed were more likely to report they would offer oral contraceptives (91% versus 75.0%, OR 3.4 [95% CI 1.44–8.48], p = 0.002) for women in the deployed setting compared to those who have not deployed. More timely (<2 weeks) access to subdermal implant insertion was associated with a greater rate of offering subdermal implants (91.9% versus 79.6%, p = 0.02). When discussing contraceptive options with all women, 27.3% of physicians do not prescribe emergency contraception because of training, ethical, and/or religious reasons. Some reported they would neither prescribe nor refer women for the following methods: emergency contraception (4.5%), intrauterine contraception (9.3%), and subdermal implants (7.3%). Conclusions: The results of this study support the need to develop a consistent, standardized, and evidence-based pre-deployment process and expanded resources in deployed environments for services related to the provision of reproductive health. Optimal strategies may aim to reduce barriers to care and enable the highest quality of health care through provider education, resource allocation, revised appointment times and content, and diversity among provider experience. Further research is needed to determine the influence of physician practice patterns on patient reproductive health outcomes and interventions to modify these practices to improve patient outcomes and military readiness.